Secondary nucleation in polymer crystallization: A kinetic view. Issue 3 (6th February 2021) - Zhang, Shujing; Wang, Zhiqi; Guo, Baohua; Xu, Jun
Abstract: Secondary nucleation on the surfaces of growing crystals plays a vital role in polymer crystallization, which determines the lamellar thickness at growth front and the radial growth rate. Though secondary nucleation has been intensively studied in the past decades, our understanding on the molecular mechanism and kinetics is not yet complete. In this perspective, we will briefly review the major advances in the secondary nucleation of flexible polymer chains in the past decade and discuss some remained questions from a viewpoint of kinetics. The main theories, thermodynamics and kinetics of secondary nucleation are first summarized. The difference of nucleation of polymer chains from that of small molecular crystals is revealed via analysis of kinetics. Then, the interplay of various microscopic processes leading to the final crystalline structures is discussed, such as lamellar thickening versus widening, intra‐chain vs inter‐chain nucleation, secondary nucleation versus lateral spreading, secondary vs primary nucleation, nucleation of polymorphisms, and so forth. Finally, some remained open questions are highlighted. Combining kinetic theory considering various microscopic processes and new experimental evidences at different length and time scales would greatly help deepen our understanding on the secondary nucleation during crystallization of flexible polymer chains. Abstract : This perspective attempts to provide a kinetic view on theories, recent advances, some open questions, and future directions on secondary nucleation of flexible polymer chains on the crystal growth front. Thermodynamic and kinetic factors affecting secondary nucleation are briefly discussed. The crystalline structures are determined by the interplay of various kinetic processes, such as attaching versus detaching, inter‐chain versus intra‐chain nucleation, thickening, and widening, etc.